The U.S. Cybersecurity and Intelligence Analysis Challenges - Weaver, John Michael (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
One of the prevailing issues regarding security to North America and more pointedly, the United States, gravitates on the topic of cyber threats confronting this nation. These threats are becoming more disruptive and destructive and many nations' infrastructure is vulnerable to them. This book makes use of a qualitative research methodology looking at a conventional understanding of the four instruments of power that include diplomacy, information, military and economic (D.I.M.E.) efforts through the use of the York Intelligence Red Team Model-Cyber (Modified) and seeing how adversaries are using them against the United States. Moreover, this project uses secondary data and makes use of the Federal Secondary Data Case Study Triangulation Model to ensure a balance of sources to dissect the problem. John M. Weaver is Associate Professor of Intelligence Analysis at York College of Pennsylvania, the US.
Chapter 1 Introduction and Background -- Chapter 2 Research Questions, Methodology, and Limitations -- Chapter 3 The United States (an Overview) -- Chapter 4 Al Qaeda -- Chapter 5 People's Republic of China (PRC) -- Chapter 6 Islamic Republic of Iran (Iran) -- Chapter 7 Islamic State (IS) -- Chapter 8 Democratic People's Republic of Korea (DPRK) -- Chapter 9 Russian Federation (Russia) -- Chapter 10 Analysis and Findings -- Chapter 11 Conclusion.
Keywords: Security, International; International Security Studies